Research guidelines for embryoids. Issue 12 (5th January 2021) - Piotrowska, Monika
Abstract : Human embryo models formed from stem cells—known as embryoids—allow scientists to study the elusive first stages of human development without having to experiment on actual human embryos. But clear ethical guidelines for research involving embryoids are still lacking. Previously, a handful of researchers put forward new recommendations for embryoids, which they hope will be included in the next set of International Society for Stem Cell Research guidelines. Although these recommendations are an improvement over the default approach, they are nonetheless unworkable, because they rely on a poorly conceived notion of an embryoid's 'potential' to trigger stringent research regulations.